Interest and Achievement of Learning In History Subject Through Implementation of Practice Field Experience Students of SMK Muhammadiyah 1 Palu in Central Sulawesi Museum - Asrianingsih; Abdul Latief, Juraid; Suyuti; Misnah; Najamuddin, Lukman; Sadi, Haliadi (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
This research discussed about: 1) the process of implementing practical field experience conducted by students of SMK Muhammadiyah 1 Palu at the Central Sulawesi Museum; 2) students' interest in learning at SMK Muhammadiyah 1 Palu in the implementation of practical field experience at the Central Sulawesi Museum; and 3) student achievement of SMK Muhammadiyah 1 Palu on the implementation of practical field experience at the Central Sulawesi Museum. The research method used is descriptive qualitative with data collection techniques through observation, interviews, documentation, and literature study. The interviews were aimed at teachers who teach history, school principals, and students at SMK Muhammadiyah 1 Palu. Processing techniques and data analysis techniques are carried out in three stages, namely data reduction, data presentation and data verification. The results of the study revealed that the implementation of practical field experience by students of SMK Muhammdiyah 1 Palu in the Central Sulawesi museum was seeing and observing various collections of historical relics. Implementation of field experience practice at the Central Sulawesi Museum in history learning can reduce boredom, increase interest in learning, be fun, interesting, not boring, add insight and knowledge and generate new enthusiasm in students in learning history. The results of the questionnaire explained that the implementation of practical field experience at the Central Sulawesi Museum could improve student achievement. This is indicated by the completeness percentage of class X Tkj A and X Tkj B reaching 95.8%.